The design of refrigeration equipment for low temperature testing rooms - Bowen, Elmo L. (Virginia Polytechnic Institute, 1954)
During World War II, with the armed forces waging war on several fronts and with the development of high altitude aircraft, the necessity for a great deal of low temperature testing was brought about. The production testing of various instruments and appliances, such as radios, cameras, clocks, and meters, which would be subjected to low temperatures in arctic climates or at high altitudes, was found necessary. This subject had been given very little consideration prior to the war. When it became necessary to test equipment at a low temperature, it was normally transported to a cold climate and there the tests were conducted. With the increased demand for low temperature testing, the expense and time delay encountered in such movements became prohibitive. During and since the war many low temperature test chambers have been built. The design problems encountered, such as load determination, defrosting, lubrication, refrigerant selection, proper staging, and control selection, have been similar, but the solutions have been different. Moore, Gellalles, and Young state: "Experience has shown that research requirements change so quickly and so radically that the original design specification cannot be much more than a hopeful guess.(22) Mr. Coy W. Brown states: "Any systems requiring evaporating refrigerant temperatures below -40° F. should be attempted only by engineers experienced in this presently special field."(5) Since definite data on equipment for low temperature test rooms seems to be limited, it is believed that from a design of such a machine much valuable information can be gained. Two low temperature testing rooms have been constructed in the Mechanical Engineering Laboratory at The Virginia Polytechnic Institute. One will operate at temperatures down to 0° F. and the other will operate at temperatures down to -40° F. In addition to being used for low temperature research, it is anticipated that the refrigerating equipment for these rooms will be used by students taking Mechanical Laboratory in routine ...